Granulocyte colony-stimulating factor stabilizes cardiac electrophysiology and decreases infarct size during cardiac ischaemic/reperfusion in swine - Kanlop N. (2014)
Aim: Effects of granulocyte colony-stimulating factor (G-CSF) on cardiac electrophysiology during ischaemic/reperfusion (I/R) period are unclear. We hypothesized that G-CSF stabilizes cardiac electrophysiology during I/R injury by prolonging the effective refractory period (ERP), increasing the ventricular fibrillation threshold (VFT) and decreasing the defibrillation threshold (DFT), and that the cardioprotection of G-CSF is via preventing cardiac mitochondrial dysfunction. Methods: In intact-heart protocol, pigs were infused with either G-CSF or vehicle (n=7 each group) without I/R induction. In I/R protocol, pigs were infused with G-CSF (0.33μgkg-1min-1) or vehicle (n=8 each group) for 30min prior to a 45-min left anterior descending artery occlusion and at reperfusion. Diastolic pacing threshold (DPT), ERP, VFT and DFT were determined in all pigs before and during I/R period. Rat's isolated cardiac mitochondria were used to test the protective effect of G-CSF (100nm) in H2O2-induced mitochondrial oxidative damage. Results: Neither G-CSF nor vehicle altered any parameter in intact-heart pigs. During ischaemic period, G-CSF significantly increased the DPT, ERP and VFT without altering the DFT. During reperfusion, G-CSF continued to increase the DPT without altering other parameters. The infarct size was significantly decreased in the G-CSF group, compared to the vehicle. G-CSF could also prevent cardiac mitochondrial swelling, decrease ROS production, and prevent mitochondrial membrane depolarization. Conclusion: G-CSF increases the DPT, ERP and VFT and reduces the infarct size, thus stabilizing the myocardial electrophysiology, and preventing fatal arrhythmia during I/R. The protective mechanism could be via its effect in preventing cardiac mitochondrial dysfunction. © 2011 The Authors. Acta Physiologica © 2011 Scandinavian Physiological Society.